Aluminum nitride powder and resin composition

By developing aluminum nitride powder with low oxygen content, multiple smooth surfaces and small aspect ratio, the problem of insufficient thermal conductivity and fluidity of aluminum nitride powder when filled in resin in the prior art is solved, and an efficient heat dissipation material effect is achieved.

CN119604468AActive Publication Date: 2025-03-11TOKUYAMA CORP
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202380056312.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-30
Filing Date
2023-08-29
Publication Date
2025-03-11
Estimated Expiration
2043-08-29

AI Technical Summary

Technical Problem

When existing aluminum nitride powders are filled in resin, it is difficult to meet the requirements of high thermal conductivity and good fluidity, especially in applications of medium-sized particles.

Method used

By adopting a specific manufacturing method, an aluminum nitride powder with an average particle size of 5 to 50 μm was developed, with a low oxygen content, multiple smooth surfaces and a small aspect ratio, ensuring its high thermal conductivity and good fluidity.

Benefits of technology

The resin composition with high thermal conductivity and good flowability is achieved in the resin, and is suitable for the application of high-efficiency heat dissipation materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604468A_ABST
    Figure CN119604468A_ABST
Patent Text Reader

Abstract

This aluminum nitride powder has an average particle diameter of 5-50 [mu] m and an oxygen content of 0.5 mass% or less, contains polyhedral particles having at least two smooth surfaces (a) when observed by a scanning electron microscope having a magnification of 500 times, and has an average value of the ratio (L / D) of the major axis (L) to the minor axis (D) of the polyhedral particles having a major axis (L) of 5 [mu] m or more within the range of 1-1.4. According to the present invention, it is possible to provide an aluminum nitride powder which has high thermal conductivity and good fluidity when filled in a resin to form a resin composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to aluminum nitride powder and a resin composition containing the aluminum nitride powder. Background Art

[0002] Aluminum nitride powder is widely known as a material having high thermal conductivity and excellent electrical insulation, and is used, for example, in thermal interface materials and the like. Thermal interface materials are materials used to reduce the thermal resistance of the path where heat generated from semiconductor elements escapes to a heat sink or a housing, and are used in a variety of forms such as sheets, gels, and greases. As thermal interface materials, heat dissipation materials obtained by filling a resin such as epoxy resin or silicone resin with a thermally conductive filler such as aluminum nitride are known. When aluminum nitride is filled in a resin, a method of combining a plurality of aluminum nitrides having different average particle sizes to improve thermal conductivity is known for the purpose of increasing the filling rate or facilitating the formation of a heat path. In resin, particles with large particle size can easily form a heat conduction path, but sometimes it is difficult to use them in thin heat dissipation materials. In addition, especially for spherical particles, the contact area between the particles in the resin is small, and sometimes it is difficult to form a heat conduction path. On the other hand, particles with small particle size are difficult to form a heat conduction path in the resin, and sometimes the fluidity becomes poor when filled into the resin. Therefore, aluminum nitride powder with an average particle size of about 5 to 50 μm has a high utilization value.

[0003] Patent Document 1 discloses an invention regarding an aluminum nitride powder, wherein the average particle size D of the aluminum nitride powder is 50 The aluminum nitride powder has a particle size of 15 to 200 μm, a content of particles with a particle size of 5 μm or less is 60% or less on a number basis, and has low alkaline earth metal, rare earth element, oxygen and silicon contents. It is also described that the aluminum nitride powder has excellent filling properties for polymer materials. As a method for obtaining such an aluminum nitride powder, a method of pulverizing aluminum nitride obtained by a direct nitriding method and heat-treating the powder is disclosed in the examples. The direct nitridation method is widely known as a method for synthesizing ceramics such as aluminum nitride, but the nitridation reaction generates a large amount of heat and reaches a high temperature, so the product is obtained as a bulk product. If it is used as a powder, it needs to be pulverized.

[0004] In addition, Patent Document 2 discloses an aluminum nitride powder as an aluminum nitride powder capable of improving the thermal conductivity of a heat dissipation component, characterized in that the average particle size is 20 to 50 μm, the oxygen content is less than 0.6 mass%, and the average half-value width of the diffraction peaks of the three Miller index (100) plane, (002) plane and (101) plane obtained by X-ray diffraction is less than 0.095°. Furthermore, Patent Document 3 proposes an aluminum nitride powder containing particles having smooth surfaces in order to improve the contact area between particles.

[0005] Patent Document 4 describes the average particle size (D 50 ) was used to prepare aluminum nitride powder with a particle size of 60 μm, and its filling property into resin, thermal conductivity, etc. were studied. It was also recorded that their various physical properties were good. Prior art literature Patent Literature

[0006] Patent Document 1: International Publication No. 2018 / 216591 Patent Document 2: Japanese Patent Application Publication No. 2003-119010 Patent Document 3: International Publication No. 2017 / 131239 Patent Document 4: Japanese Patent Application Publication No. 2022-067865 Summary of the invention Problems to be solved by the invention

[0007] In the above-mentioned prior art, the aluminum nitride powder disclosed in Patent Documents 1 and 4 is obtained by direct nitridation or combustion synthesis. Due to the low oxygen content in the manufacturing method, the thermal conductivity of the particles themselves is excellent. However, since the powder is obtained by crushing or disintegrating the block after the reaction, the particles constituting the powder are amorphous or firm agglomerates, and it is difficult to obtain particles with smooth surfaces. In addition, the aspect ratio (ratio (L / D) of the long diameter (L) to the short diameter (D) of the particles) of the above-mentioned particles is high, and the fluidity when filled into the resin cannot be fully satisfied due to the influence of the above-mentioned surface properties. In addition, the aluminum nitride powder disclosed in Patent Document 2 is characterized in that the aluminum nitride powder with low oxygen content is produced by heating the raw aluminum nitride powder to improve crystallinity, and the crushed powder whose fine powder promoting particle growth is limited is heat-treated to produce aluminum nitride powder with low oxygen content and a desired particle size. Therefore, the particle shape of the obtained aluminum nitride powder is amorphous, and a smooth surface is not formed due to the presence of the crushed surface. Furthermore, the aluminum nitride powder described in the above-mentioned Patent Document 3 contains particles with smooth surfaces, and although it is expected that the fluidity between particles when filled into a resin and the thermal conductivity caused by surface contact will be improved, since the oxygen concentration is high due to the manufacturing method for forming the smooth surface, there is room for improvement in the thermal conductivity of the particles themselves. As described above, in the filling of aluminum nitride powder into resin, the conventional aluminum nitride powder used as medium-sized particles cannot fully meet the demand for high heat dissipation accompanied by the increase in density of power devices in recent years, and there is room for further improvement. Therefore, an object of the present invention is to provide an aluminum nitride powder having high thermal conductivity and good fluidity when filled in a resin to form a resin composition. Means of solving problems

[0008] The inventors of the present invention have repeatedly conducted intensive studies to achieve the above-mentioned purpose. As a result, they have successfully developed an aluminum nitride powder having a low oxygen content that affects the thermal conductivity of the particles themselves, a smooth surface that is effective in improving fluidity, a small aspect ratio, and an average particle size of about 5 to 50 μm by adopting a specific production method described below, thereby completing the present invention.

[0009] The gist of the present invention is the following [1] to [6]. [1] An aluminum nitride powder having an average particle size of 5 to 50 μm and an oxygen content of 0.5 mass % or less, comprising polyhedral particles having at least two smooth surfaces when observed under a scanning electron microscope at a magnification of 500 times, and wherein the average value of the ratio L / D of the major axis L to the minor axis D of the polyhedral particles having a major axis L of 5 μm or more is in the range of 1.0 to 1.4. [2] The aluminum nitride powder according to [1] above, wherein the polyhedral particles are present in an amount of 70% or more. [3] The aluminum nitride powder according to [1] or [2], wherein in a 2000-fold SEM image of a cross section of the polyhedral particle, the average value M of the maximum value M of the perpendicular distance between the contour line of the smooth surface and the straight line connecting the ends of the contour line in 10 randomly selected particles is A It is less than 0.15μm. [4] The aluminum nitride powder according to any one of [1] to [3] above, which is used for resin filling. [5] A resin composition comprising the aluminum nitride powder according to any one of [1] to [4] above and a resin. [6] A method for producing aluminum nitride powder, comprising: Step 1: prepare a granular material having an average particle size of 0.5 to 5 μm and a specific surface area of ​​1.2 to 16.0 m 2 100 parts by mass of the first aluminum nitride powder raw material having an average particle size of 3 to 40 μm and a specific surface area of ​​0.05 to 1.8 m 2 / g, and a ratio SA2 / SA1 of the specific surface area SA2 of the second aluminum nitride powder raw material to the specific surface area SA1 of the first aluminum nitride powder raw material is 0.8 or less to prepare a raw material mixture, and In step 2, the raw material mixture is heated to 1750 to 2100° C. under supply of an inert gas. Effects of the Invention

[0010] According to the present invention, it is possible to provide an aluminum nitride powder having an average particle size of about 5 to 50 μm. Since the aluminum nitride powder has a low oxygen content, the thermal conductivity of the particles themselves is high. Furthermore, since the aluminum nitride powder has two or more smooth surfaces and a small aspect ratio, the fluidity when filled into a resin is extremely high. Furthermore, by increasing the contact area between the particles caused by the smooth surfaces, it is possible to impart extremely high thermal conductivity to a resin composition filled with the aluminum nitride powder. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] [ Figure 1 ] is a SEM observation image of the aluminum nitride powder of the present invention. [ Figure 2 ] is a SEM observation image of the aluminum nitride powder obtained in Example 26. [ Figure 3 ] is an explanatory diagram of the definition of the smooth surface of the particles constituting the aluminum nitride powder of the present invention. DETAILED DESCRIPTION

[0012] [Aluminum nitride powder] The aluminum nitride powder of the present invention has an average particle size of 5 to 50 μm and an oxygen content of 0.5 mass % or less. When observed under a scanning electron microscope at a magnification of 500 times, the powder contains polyhedral particles having at least two smooth surfaces, and the average value of the ratio (L / D) of the major axis (L) to the minor axis (D) of the polyhedral particles having a major axis L of 5 μm or more is in the range of 1.0 to 1.4.

[0013] <polyhedral particles> Figure 1 The figure shows an image of the aluminum nitride powder of the present invention observed by a scanning electron microscope at a magnification of 500. The aluminum nitride powder is composed of a plurality of aluminum nitride particles, including a plurality of polyhedral particles such as polyhedral particles 11 and polyhedral particles 12. Polyhedral particle 11 is a polyhedral aluminum nitride particle having at least two smooth surfaces a randomly present. Polyhedral particle 12 is also an aluminum nitride particle having at least two smooth surfaces a. Figure 1 In addition to the polyhedral particle 11 and the polyhedral particle 12, there are a plurality of polyhedral particles.

[0014] The smooth surface a of the multifaceted particle is Figure 1As shown, it is a smooth surface that is confirmed to have no concavo-convex structure in the surface during observation under a scanning electron microscope at a magnification of 500 times, and is a surface derived from the crystal growth surface of aluminum nitride. In addition, the smooth surface a is different from the crushed surface formed by crushing aluminum nitride particles. The crushed surface is inferior in smoothness to the smooth surface, and the concavo-convex structure derived from the crushing is observed during observation under a scanning electron microscope, so it can be distinguished from the smooth surface. In addition, the smoothness of the above-mentioned smooth surface a is described in more detail in the examples. In a 2000-fold SEM image of the cut surface of the particle, in arbitrarily selected 10 particles, the maximum value of the vertical distance between the contour line corresponding to the smooth surface and the straight line connecting the ends of the above-mentioned contour line is set to M, and among the M measured for the above-mentioned 10 particles respectively, the maximum value M max The particle size M of 10 particles is preferably 0.3 μm or less, and more preferably 0.2 μm or less. A More preferably, it is 0.15 μm or less. Incidentally, the crushed surface generated by crushing the aluminum nitride block is smooth. max Including the concave and convex and convex not less than 0.3μm, in addition, the average value of the above maximum value M A Not less than 0.15μm.

[0015] The aluminum nitride powder of the present invention contains polyhedral particles, which can easily improve the thermal conductivity of the resin composition when filled into the resin. Although the reason is uncertain, it is believed that the presence of polyhedral particles having multiple smooth surfaces increases the contact area between particles in the resin, making it easier to form a heat conduction path. In addition, the presence of the smooth surface also improves the fluidity of the particles, which can also help improve the filling property when filling into the resin.

[0016] In the present invention, as long as the number of smooth surfaces possessed by the polyhedral particles is 2 or more, there is no particular limitation, but from the viewpoint of increasing the contact area between particles when filled into the resin, it is preferably 3 or more. In addition, the upper limit of the smooth surface possessed by the polyhedral particles is not particularly limited, for example, 10. It should be noted that the number of smooth surfaces possessed by the polyhedral particles is determined based on an image obtained by observation with a scanning electron microscope (SEM) at a magnification of 500 times. Furthermore, it is preferable that two continuous smooth surfaces are continuous so as to form a hilly portion.

[0017] From the viewpoint of increasing the contact area between particles when filled into the resin to improve the thermal conductivity, the area of ​​each smooth surface of the multifaceted particle is preferably large to a certain extent. From this viewpoint, the multifaceted particle preferably has at least two smooth surfaces with an area of ​​2 to 1600 μm. 2 The smooth surface preferably has at least 3 areas of 2 to 1600 μm2 smooth surface. The area of ​​the smooth surface was determined from an image observed with a scanning electron microscope (SEM) at a magnification of 500 times.

[0018] From the viewpoint of improving the thermal conductivity of the resin composition obtained by filling the aluminum nitride powder into the resin, the presence ratio of the polyhedral particles in the aluminum nitride powder of the present invention is preferably 70% or more, more preferably 80% or more, and further preferably 90% or more. The presence ratio of the polyhedral particles is the ratio of the total area of ​​the polyhedral particles to the total area of ​​all aluminum nitride particles determined in an image observed by a scanning electron microscope at a magnification of 500 times.

[0019] As described above, the smooth surface possessed by multi-faceted particles is different from the broken surface having bumps or undulations on the surface. When an aluminum nitride powder having fewer particles having broken surfaces is used, the fluidity of the resin composition filled in the resin tends to be improved. Therefore, the presence ratio of particles having broken surfaces in the aluminum nitride powder of the present invention is preferably 20% or less, more preferably 10% or less. The presence ratio of particles having broken surfaces is the ratio of the total area of ​​particles having broken surfaces to the total area of ​​all aluminum nitride particles determined in an image observed with a scanning electron microscope at a magnification of 500 times.

[0020] <Major diameter / minor diameter ratio of polyhedral particles> The average value of the ratio (L / D) of the long diameter (L) to the short diameter (D) of the polyhedral particles of the aluminum nitride powder of the present invention with a long diameter (L) of 5 μm or more is in the range of 1.0 to 1.4. When the above ratio (L / D) exceeds 1.4, the fluidity of the resin composition obtained by filling the aluminum nitride powder into the resin is easily reduced, and the workability, etc. are deteriorated. From the viewpoint of improving the fluidity of the resin composition, the average value of the ratio (L / D) of the major axis (L) to the minor axis (D) of the polyhedral particles having a major axis (L) of 5 μm or more is preferably 1.0 to 1.3, more preferably 1.0 to 1.2. Here, the major axis (L) and minor axis (D) of the polyhedral particle are determined based on the shape of the polyhedral particle observed by a scanning electron microscope at a magnification of 500 times. The major diameter (L) is defined as the maximum distance between any two points on the periphery of the polyhedral particle. The minor diameter (D) is a line segment perpendicular to the major diameter (L) and is defined as a line segment passing through the midpoint of the major diameter (L) and two points on the periphery of the polyhedral particle. In addition, the average value of the ratio (L / D) of the major diameter (L) to the minor diameter (D) is calculated by obtaining the ratio (L / D) for at least 20 polyhedral particles having a major diameter (L) of 5 μm or more and calculating their average value. The aluminum nitride powder containing polyhedral particles of the present invention can be obtained, for example, by the production method described below.

[0021] <Average particle size> The average particle size of the aluminum nitride powder of the present invention is 5 to 50 μm. Such aluminum nitride powder having a moderate average particle size is easy to be used for filling in resin, and therefore has great utilization value. If the average particle size is too large, it is sometimes difficult to use, for example, in a thin heat release material, and if the average particle size is too small, there is a tendency for the thermal conductivity to decrease. The average particle size of the aluminum nitride powder of the present invention is preferably 5 to 40 μm, and more preferably 5 to 30 μm. In this specification, the average particle size of the aluminum nitride powder refers to the particle size (D 50 ).

[0022] <Oxygen content> The oxygen content of the aluminum nitride powder of the present invention is 0.5 mass % or less. In addition, the oxygen content is the total oxygen content measured by the high-temperature thermal decomposition method described in the Examples. When the oxygen content exceeds 0.5% by mass, the thermal conductivity of the aluminum nitride powder decreases, and thus the thermal conductivity of the resin composition filled with the aluminum nitride powder also decreases. The oxygen content of the aluminum nitride powder is preferably 0.4% by mass or less, more preferably 0.3% by mass or less, and further preferably 0.2% by mass or less. Such polyhedral particles having a low oxygen concentration are provided for the first time by the present invention, and thus the aluminum nitride powder of the present invention exhibits a high thermal conductivity as shown below.

[0023] <Thermal conductivity> The thermal conductivity of the aluminum nitride powder of the present invention is preferably 80 W / m·K or more, more preferably 120 W / m·K or more, and further preferably 160 W / m·K or more. Since the thermal conductivity of the aluminum nitride powder itself is so high, the thermal conductivity of the resin composition when filled in the resin is also high, and excellent heat dissipation can be exerted. The higher the thermal conductivity of the aluminum nitride powder, the better, but it is generally 230 W / m·K or less. The thermal conductivity of the aluminum nitride powder can be adjusted by the oxygen content, etc. The thermal conductivity of the aluminum nitride powder was measured by micro-Raman spectroscopy, and the details are described in the examples.

[0024] [Method for producing aluminum nitride powder] The method for producing the aluminum nitride powder of the present invention is not particularly limited as long as it is a method that can obtain an aluminum nitride powder containing the polyhedral particles and having the above-mentioned average particle size and oxygen content, but a method including the following steps 1 and 2 is preferred. Step 1: average particle size 0.5 to 5 μm, specific surface area 1.2 to 16.0 m 2 100 parts by mass of the first aluminum nitride powder raw material having an average particle size of 3 to 40 μm and a specific surface area of ​​0.05 to 1.8 m 2 / g, and a ratio (SA2 / SA1) of the specific surface area (SA2) of the second aluminum nitride powder raw material to the specific surface area (SA1) of the first aluminum nitride powder raw material is less than 0.8 to prepare a raw material mixture. Step 2: A step of heating the raw material mixture to 1750° C. to 2100° C. under supply of an inert gas.

[0025] <Process 1> Step 1 is to prepare a particle with an average particle size of 0.5 to 5 μm and a specific surface area of ​​1.2 to 16.0 m 2 100 parts by mass of the first aluminum nitride powder raw material having an average particle size of 3 to 40 μm and a specific surface area of ​​0.05 to 1.8 m 2 / g, and a ratio (SA2 / SA1) of the specific surface area (SA2) of the second aluminum nitride powder raw material to the specific surface area (SA1) of the first aluminum nitride powder raw material is less than 0.8 to prepare a raw material mixture. The raw material mixture contains aluminum nitride having different average particle sizes in a predetermined amount, and is subjected to a heating step (step 2) described later, thereby obtaining the aluminum nitride powder of the present invention. That is, it is believed that by the presence of an appropriate amount of the second aluminum nitride powder raw material having a relatively large average particle size, the first aluminum nitride powder raw material having a small average particle size enters the second aluminum nitride powder raw material through a sublimation reaction during the heating process, and the second aluminum nitride powder raw material crystallizes and grows, and the particle size becomes larger. It is also estimated that the polyhedral particles specified above are formed through such crystal growth. It is further estimated that since the oxygen present in the first aluminum nitride powder can be effectively removed through the above-mentioned sublimation reaction, the oxygen concentration of the aluminum nitride powder of the present invention produced through the heating process becomes low. On the other hand, when the first and second aluminum nitride powder raw materials are not used in the predetermined blending amounts as described above, insufficient growth of particles or agglomeration between particles may occur, making it difficult to obtain the aluminum nitride powder of the present invention.

[0026] The average particle size of the first aluminum nitride powder raw material is 0.5 to 5 μm, and the specific surface area is 1.2 to 16.0 m 2 / g, preferably with an average particle size of 0.7 to 5 μm and a specific surface area of ​​1.2 to 12.0 m 2 / g. The average particle size of the second aluminum nitride powder raw material is 3 to 40 μm, and the specific surface area is 0.05 to 1.8 m 2 The average particle size of the second aluminum nitride powder raw material can be appropriately selected according to the average particle size of the aluminum nitride powder of the present invention to be produced, and is preferably 3 to 20 μm, and more preferably 5 to 15 μm. The amount of the second aluminum nitride powder raw material in the raw material mixture is 1 to 20 parts by mass, preferably 2 to 15 parts by mass, and more preferably 3 to 10 parts by mass, relative to 100 parts by mass of the first aluminum nitride powder raw material. As described above, the aluminum nitride powder of the present invention can be obtained by appropriately adjusting the amounts of the first and second aluminum nitride powder raw materials.

[0027] The ratio (SA2 / SA1) of the specific surface area (SA2) of the second aluminum nitride powder raw material to the specific surface area (SA1) of the first aluminum nitride powder raw material is 0.8 or less. In this way, by adjusting the specific surface area ratio (SA2 / SA1), the aluminum nitride powder of the present invention can be easily obtained. The above-mentioned specific surface area ratio (SA2 / SA1) is preferably 0.7 or less, and more preferably 0.6 or less.

[0028] In order to promote the growth of particles, an additive that promotes the growth of particles may be added during the calcination. The additive is not particularly limited, and oxides, fluorides, chlorides, etc. of alkali metals, alkaline earth metals, or rare earth elements may be used.

[0029] As long as the first and second aluminum nitride powder raw materials have a specified average particle size, generally used aluminum nitride powders can be used without particular restrictions. They can be aluminum nitride powders produced by a reduction nitridation method, aluminum nitride powders produced by a direct nitridation method such as a combustion synthesis method and adjusted to a specified average particle size through a crushing and classification process, or aluminum nitride powders produced by production methods other than these. It is also preferred that the aluminum nitride powder of the present invention produced through steps 1 and 2 is used as a second aluminum nitride powder raw material and steps 1 and 2 are performed again to obtain the aluminum nitride powder of the present invention having a larger average particle size.

[0030] <Process 2> Step 2 is a step of heating the raw material mixture prepared in step 1 to 1750 to 2100° C. under supply of an inert gas. When the heating temperature is lower than 1750°C, the crystal growth of the aluminum nitride particles cannot be promoted, and it is difficult to obtain an aluminum nitride powder containing aluminum nitride particles having a smooth surface. On the other hand, when the heating temperature exceeds 2100°C, fusion bonding between the particles is likely to occur. From this point of view, the heating temperature is preferably 1750 to 2100°C, more preferably 1800 to 2050°C, and even more preferably 1800 to 2000°C. In addition, the heating time is not particularly limited, but is preferably 1 to 20 hours, and more preferably 2 to 15 hours. When the heating time is shorter than 1 hour, the crystal growth of the aluminum nitride particles cannot be fully carried out, and it is difficult to form a smooth surface. On the other hand, even if the heating exceeds 20 hours, the particles are difficult to continue to grow, which is disadvantageous in industrial implementation.

[0031] The heating is carried out under the supply of an inert gas. That is, it is most preferred to supply an inert gas to a heating device for accommodating the raw material mixture and heating the raw material mixture, but the heating can also be carried out while continuously supplying the inert gas. In addition, the raw material mixture is filled in a heating container (hereinafter also referred to as a "container") and accommodated in the above-mentioned heating device. As the above-mentioned container, a carbon container is preferably used. In addition, as an inert gas, argon gas and nitrogen gas are generally used, among which nitrogen gas is preferably used.

[0032] <Other Processes> After step 2, a crushing step may be performed as needed. The crushing step is performed to break the bonds between loosely bonded aluminum nitride particles, and is different from the pulverization step in which the aluminum nitride particles are partially crushed. Therefore, even if the crushing step is performed, the shape of the polyhedral particles can be maintained, and particles with broken surfaces are hardly generated. The crushing can be carried out by a known method, for example, a roll crusher, a pin crusher, a vibration mill, a jet mill, a ball mill, a mass crusher, a jaw crusher, or the like.

[0033] Alternatively, an oxidation step may be performed after step 2, and the oxidation step is preferably performed after the above-mentioned crushing step. By performing the oxidation step, decomposition due to contact with water or the like can be prevented. The oxidation step can be performed by heating in an air atmosphere. The heating temperature in the oxidation step is not particularly limited, but is preferably 500 to 900° C., more preferably 600 to 800° C. The heating time is not particularly limited, but is preferably 1 to 20 hours, more preferably 5 to 15 hours. The oxygen content of the oxide film formed in the above oxidation step is included in the oxygen content of the aluminum nitride powder. By performing the oxidation step in a manner so that the oxygen content does not exceed the range of the oxygen content of the aluminum nitride powder, when filled into the resin, excellent thermal conductivity can be imparted to the obtained resin composition.

[0034] In order to improve compatibility with resins, water resistance, etc., the aluminum nitride powder of the present invention can be subjected to surface treatment as required. The surface treatment can be carried out by a known method. For example, the surface treatment can be carried out using silicone oil, a silylating agent, a silane coupling agent and other organic silicon compounds, acids such as phosphoric acid, phosphates, and fatty acids, polymer compounds such as polyamide resins, inorganic substances such as aluminum oxide and silicon dioxide, etc.

[0035] <Purpose> The use of the aluminum nitride powder of the present invention is not particularly limited, and it can be used as a raw material for an aluminum nitride substrate, preferably as a resin filling. The aluminum nitride powder of the present invention is preferably filled into a resin and used as a resin composition containing a resin and aluminum nitride powder. As described above, the aluminum nitride powder of the present invention has a low oxygen content, the aluminum nitride powder itself has a high thermal conductivity, and contains multi-faceted particles with multiple smooth surfaces, so the contact area between the particles is large, so it is easy to effectively form a heat conduction path in the resin composition. Therefore, the thermal conductivity of the resin composition is improved, and it can be suitable for use as a heat dissipation material.

[0036] The resin contained in the resin composition is not particularly limited, and examples thereof include: epoxy resin, epoxy resin with mesogen group introduced, unsaturated polyester resin, polyimide resin, phenolic resin and other thermosetting resins, polyethylene, polypropylene, polyamide, polycarbonate, polyphenylene sulfide and other thermoplastic resins, ethylene propylene rubber, styrene butadiene rubber and other rubbers, silicone resins and the like. Among them, epoxy resins and silicone resins are preferred.

[0037] The content of the aluminum nitride powder of the present invention contained in the resin composition is not particularly limited, but is preferably 600 to 2500 parts by mass, more preferably 1000 to 2500 parts by mass, relative to 100 parts by mass of the resin. When the content of the aluminum nitride powder is above these lower limits, the thermal conductivity of the resin composition is improved, and when the content of the aluminum nitride powder is below these upper limits, the fluidity of the resin composition is improved, and the handling properties such as moldability are improved.

[0038] The resin composition may contain fillers other than the aluminum nitride powder of the present invention within a range not inhibiting the effects of the present invention. Examples of other fillers include aluminum oxide, zinc oxide, boron nitride, silicon nitride, silicon carbide, graphite, and the like, in addition to aluminum nitride powder that does not satisfy the conditions of the present invention. The mixing ratio of the aluminum nitride powder of the present invention and other fillers can be appropriately adjusted within the range of 1:99 to 99:1.

[0039] The resin composition may contain additives such as a plasticizer, a vulcanizing agent, a curing accelerator, and a release agent as necessary.

[0040] The resin composition can be prepared by mixing the components with a stirrer or a mixer. The resin composition thus obtained can be made into a heat dissipation material in a desired form such as a heat sink or a heat dissipation paste by a known molding method. Examples of molding methods include extrusion molding, compression molding, a scraper method, and a resin impregnation method. After molding, heat curing, photocuring, etc. can be performed as required. Example

[0041] Hereinafter, although an Example is shown in order to demonstrate this invention more concretely, this invention is not limited to these Examples.

[0042] [Measurement method] Various physical properties in Examples and Comparative Examples were measured by the following methods. (1) Average particle size and specific surface area Average particle size (D 50 ) Aluminum nitride powder was dispersed in an aqueous sodium pyrophosphate solution using a homogenizer and the particle size distribution was measured using a laser diffraction particle size distribution apparatus ("MICROTRAC HRA" manufactured by Nikkiso Co., Ltd.). The specific surface area was determined by the BET method using N2 adsorption using a flow type surface area automatic measuring device FlowSorb 2300 manufactured by Shimadzu Corporation.

[0043] (2) The presence and proportion of polyhedral particles A scanning electron microscope (TM3030 manufactured by Hitachi High-Technologies Corporation) was used to take SEM photographs of the aluminum nitride powder at a magnification of 500 times (accelerating voltage 15 kV, secondary electron detection). The SEM photographs were used to confirm the presence of particles having two or more smooth surfaces and to determine the presence of polyhedral particles. In addition, the existence ratio of polyhedral particles is calculated by calculating the ratio of the total area of ​​polyhedral particles to the total area of ​​all aluminum nitride particles obtained by image analysis of the above-mentioned SEM photograph, and taking it as the existence ratio of polyhedral particles. The number of fields of view of the SEM photograph is more than 10. Specifically, it is calculated by the following formula. Existence ratio of polyhedral particles (%) = [(total area of ​​polyhedral particles) / (total area of ​​all aluminum nitride particles)] × 100

[0044] (3) Ratio of the long diameter (L) to the short diameter (D) of polyhedral particles (L / D) According to the SEM photographs obtained in (2) above, for 20 polyhedral particles with a long diameter (L) of 5 μm or more, the ratio of the long diameter (L) to the short diameter (D) was calculated, and their average value was calculated as the ratio (L / D) of the long diameter (L) to the short diameter (D) of the polyhedral particles. In the case of the aluminum nitride powder in which no polyhedral particles were observed in the comparative example, the ratio (L / D) was determined by the same method as described above with respect to particles having a major diameter (L) of 5 μm or more.

[0045] (4) Evaluation of smoothness of smooth surface Aluminum nitride powder is filled into acrylic resin, and after curing, it is cut at an arbitrary position. In the 2000-fold SEM image of the cut surface, any 10 particles with smooth surfaces are selected. Figure 3 As shown, a straight line L is drawn connecting the end P1 and the end P2 of the contour line forming the smooth surface, and the maximum value of the vertical distance between the straight line L and the contour line is set as M, and the maximum value of the values ​​of M measured in the 10 particles selected above is set as M. max。 In addition, the average value of the above M is represented as M A .

[0046] (5) Oxygen content The oxygen content of the aluminum nitride powder was measured using an oxygen-nitrogen analyzer "EMGA-620W" manufactured by Horiba, Ltd., from the amount of CO gas generated by a high-temperature thermal decomposition method in a graphite crucible to measure the oxygen content (oxygen concentration) contained in the aluminum nitride powder.

[0047] (6) Thermal conductivity of aluminum nitride powder The thermal conductivity of the aluminum nitride powder was measured based on the micro-Raman spectroscopy method described in Japanese Patent Application Laid-Open No. 2021-143968. The details are as follows.

[0048] (Preparation of calibration curve) The following aluminum nitride sintered bodies S1 to S4 were used as samples for preparing the calibration curve. S1: Commercially available product, relative density 99% or more, hexagonal system, thermal conductivity determined by laser flash method: 90 W / m·K S2: Commercially available product, relative density 99% or more, hexagonal system, thermal conductivity determined by laser flash method: 175 W / m·K S3: Commercially available product, relative density 99% or more, hexagonal system, thermal conductivity determined by laser flash method: 200 W / m·K S4: Commercially available product, relative density 99% or more, hexagonal system, thermal conductivity determined by laser flash method: 239 W / m·K

[0049] The Raman spectra of commercially available aluminum nitride sintered body samples S1 to S4 were obtained using a micro-Raman spectrometer (NRS-7100, manufactured by Japan Spectroscopy) at an excitation wavelength of 532 nm, an output power of 10.9 to 11.0 mW, an objective lens of 100 times, a measurement time of 30 seconds × 2 accumulations, a grating of 3000 lines / mm, a slit of 10 × 1000 μm, an aperture of 4000 μm, and a spectral resolution of 0.47 cm -1 The Raman spectrum was obtained under the conditions of 1 μm spot diameter and 500 mm focal length. E2, one of the peaks inherent to aluminum nitride, was found. H The peak of the mode (655cm -1 The peak half-value width (half-value width) of the peak near the peak (the peak near the peak) is measured at 6 locations for one sample, and the average value is taken as the peak half-value width of the sample.

[0050] Next, the thermal conductivity of the aluminum nitride sintered body sample whose peak half value width was measured was determined by a laser flash method. The relationship between the obtained thermal conductivity and the peak half-value width was plotted and confirmed. As a result, the logarithm of the peak half-value width was proportional to the logarithm of the thermal conductivity, and a calibration curve represented by the following formula was obtained. log(λ)=Alog(W)+B In the above formula, λ is the thermal conductivity, W is the peak half-value width, A is -2.25, and B is 3.50.

[0051] (Measurement of thermal conductivity) The thermal conductivity of the aluminum nitride powder obtained in each example and comparative example was measured using a micro Raman spectrometer (manufactured by JASCO Corporation: NRS-7100). The measurement conditions were: excitation wavelength 532nm, output power 10.9-11.0mW, objective lens 100 times, measurement time 30 seconds × 2 accumulations, grating 3000 lines / mm, slit 10×1000μm, aperture 4000μm, spectral resolution 0.47cm -1 , spot diameter 1 μm, spectrometer focal length 500 mm. The measurement is as follows: an aluminum nitride powder sample dispersed on a glass slide by waving is observed using an optical microscope, particles with a particle size close to the average particle size of the above powder are selected, the focus is on the surface, and Raman spectroscopy is performed. In the obtained Raman spectrum, E2, one of the peaks inherent to aluminum nitride, was selected. H The peak of the mode (655cm -1 The peak half-value width of the peak is determined by measuring the peak half-value width of 6 particles for one sample, and the average value is taken as the peak half-value width of the sample. The thermal conductivity of the aluminum nitride powder is calculated from the obtained peak half-value width and the above calibration curve.

[0052] (7) Thermal conductivity of resin composition 100 parts by mass of aluminum nitride powder and 10 parts by mass of resin were mixed to obtain a resin composition. Epoxy resin was used as the resin. The resin composition was hot-pressed at 100° C. to obtain a sheet having a thickness of 1 mm. The thermal conductivity of the obtained sheet was measured by a laser flash method. (8) Flowability of resin composition The resin composition obtained in the above (7) was measured for its discharge amount per minute (g / min) using a syringe "PSY-30F" manufactured by Musashi Engineering Co., Ltd. The inner diameter of the main body of the storage syringe sample was 22 mm, and the inner diameter of the tip portion of the sample discharge was 2 mm. The discharge pressure was 0.62 Pa.

[0054] (Example 1) The average particle size is 0.5 μm and the specific surface area is 15.7 m 2 / g aluminum nitride powder raw material 100 parts by mass with an average particle size of 3.2 μm and a specific surface area of ​​1.68 m 2 1 part by mass of aluminum nitride powder raw materials of 0.1 / g were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 1950°C for 4 hours. The heating was carried out under normal pressure. The obtained aluminum nitride powder was crushed with a planetary ball mill and oxidized at 700°C for 8 hours in an atmospheric atmosphere to obtain an average particle size of 5.0 μm and a specific surface area of ​​0.96 m 2 / g aluminum nitride powder (AL-1). The crushing and oxidation treatments were performed in the same manner in all the following examples, and thus are omitted below. The various measurement results of the aluminum nitride powder are shown in Table 1.

[0055] (Example 2) The average particle size is 1.0 μm and the specific surface area is 2.81 m 2 / g aluminum nitride powder raw material 100 parts by mass, average particle size 3.0 μm, specific surface area 1.79 m 2 5 parts by mass of aluminum nitride powder raw material having a value of / g and 0.1 parts by mass of sulfur as an additive were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 1800°C for 20 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain a granular material with an average particle size of 6.9 μm and a specific surface area of ​​0.70 m 2 Table 1 shows the various measurement results of the aluminum nitride powder.

[0056] (Example 3) The average particle size is 1.0 μm and the specific surface area is 2.81 m 2 / g aluminum nitride powder raw material 100 parts by mass, average particle size 3.0 μm, specific surface area 1.79 m 2 5 parts by mass of a raw material of aluminum nitride powder having a concentration of 100 / g and 0.1 parts by mass of yttrium oxide as an additive were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 1800°C for 20 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain a granular material with an average particle size of 7.0 μm and a specific surface area of ​​0.69 m 2 Table 1 shows the various measurement results of the aluminum nitride powder.

[0057] (Example 4) The average particle size is 1.0 μm and the specific surface area is 2.81 m 2 / g aluminum nitride powder raw material 100 parts by mass, average particle size 3.0 μm, specific surface area 1.79 m 2 5 parts by mass of a raw material of aluminum nitride powder having a value of / g and 0.1 parts by mass of calcium fluoride as an additive were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 1800°C for 20 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain a granular material with an average particle size of 7.0 μm and a specific surface area of ​​0.69 m 2 Table 1 shows the various measurement results of the aluminum nitride powder.

[0058] (Example 5) The average particle size is 1.0 μm and the specific surface area is 2.81 m 2 / g aluminum nitride powder raw material 100 parts by mass and an average particle size of 3.2 μm and a specific surface area of ​​1.68 m 2 5 parts by mass of aluminum nitride powder raw materials with a concentration of / g were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 2100°C for 1 hour. The heating was carried out under normal pressure, and then crushed and oxidized to obtain a granular material with an average particle size of 7.1 μm and a specific surface area of ​​0.68 m 2 Table 1 shows the various measurement results of the aluminum nitride powder.

[0059] (Example 6) The average particle size is 1.0 μm and the specific surface area is 2.81 m 2 / g aluminum nitride powder raw material 100 parts by mass, average particle size 3.0 μm, specific surface area 1.79 m2 5 parts by mass of aluminum nitride powder raw material having a value of / g and 0.1 parts by mass of calcium carbonate as an additive were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 1800°C for 20 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain a granular material with an average particle size of 7.1 μm and a specific surface area of ​​0.68 m 2 Table 1 shows the various measurement results of the aluminum nitride powder.

[0060] (Example 7) The average particle size is 1.0 μm and the specific surface area is 2.81 m 2 / g aluminum nitride powder raw material 100 parts by mass, average particle size 3.0 μm, specific surface area 1.79 m 2 5 parts by mass of a raw material of aluminum nitride powder having a value of / g and 5.0 parts by mass of sulfur as an additive were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 1800°C for 20 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain a granular material with an average particle size of 7.1 μm and a specific surface area of ​​0.68 m 2 Table 1 shows the various measurement results of the aluminum nitride powder.

[0061] (Example 8) The average particle size is 1.0 μm and the specific surface area is 2.81 m 2 / g aluminum nitride powder raw material 100 parts by mass, average particle size 3.0 μm, specific surface area 1.79 m 2 5 parts by mass of a raw material of aluminum nitride powder having a concentration of / g and 0.1 parts by mass of cesium oxide as an additive were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 1800°C for 20 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain a granular material with an average particle size of 7.2 μm and a specific surface area of ​​0.67 m 2 Table 1 shows various measurement results of the aluminum nitride powder.

[0062] (Example 9) The average particle size is 1.0 μm and the specific surface area is 2.81 m 2 / g aluminum nitride powder raw material 100 parts by mass, average particle size 3.0 μm, specific surface area 1.79 m 2 5 parts by mass of aluminum nitride powder raw material having a value of / g and 0.1 parts by mass of lanthanum oxide as an additive were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 1800°C for 20 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain a granular material with an average particle size of 7.3 μm and a specific surface area of ​​0.66 m 2 Table 1 shows the various measurement results of the aluminum nitride powder.

[0063] (Example 10) The average particle size is 1.0 μm and the specific surface area is 2.81 m 2 / g aluminum nitride powder raw material 100 parts by mass and an average particle size of 3.2 μm and a specific surface area of ​​1.68 m 2 5 parts by mass of aluminum nitride powder raw materials with a concentration of / g were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 2000°C for 2 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain a granular material with an average particle size of 7.6 μm and a specific surface area of ​​0.63 m 2 Table 1 shows various measurement results of the aluminum nitride powder.

[0064] (Example 11) The average particle size is 1.0 μm and the specific surface area is 2.81 m 2 / g aluminum nitride powder raw material 100 parts by mass and an average particle size of 5.0 μm and a specific surface area of ​​1.02 m 2 5 parts by mass of aluminum nitride powder raw materials with a concentration of / g were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 1950°C for 3 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain an average particle size of 8.0 μm and a specific surface area of ​​0.60 m 2 Table 2 shows the various measurement results of the aluminum nitride powder.

[0065] (Example 12) The average particle size is 1.0 μm and the specific surface area is 2.81 m 2 / g aluminum nitride powder raw material 100 parts by mass and an average particle size of 7.8 μm and a specific surface area of ​​0.62 m 2 10 parts by mass of aluminum nitride powder raw materials with a concentration of 100 g / g were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 1950°C for 3 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain an average particle size of 14.0 μm and a specific surface area of ​​0.27 m2 Table 2 shows the various measurement results of the aluminum nitride powder.

[0066] (Example 13) The average particle size is 0.5 μm and the specific surface area is 15.70 m 2 / g aluminum nitride powder raw material 100 parts by mass and an average particle size of 7.8 μm and a specific surface area of ​​0.62 m 2 5 parts by mass of aluminum nitride powder raw materials with a concentration of / g were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 1900°C for 10 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain a granular material with an average particle size of 16.2 μm and a specific surface area of ​​0.23 m 2 Table 2 shows the various measurement results of the aluminum nitride powder.

[0067] (Example 14) The average particle size is 0.5 μm and the specific surface area is 15.70 m 2 / g aluminum nitride powder raw material 100 parts by mass and an average particle size of 7.8 μm and a specific surface area of ​​0.62 m 2 10 parts by mass of aluminum nitride powder raw materials with a concentration of 1 g / g were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 1950°C for 5 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain an average particle size of 16.6 μm and a specific surface area of ​​0.23 m 2 Table 2 shows the various measurement results of the aluminum nitride powder.

[0068] (Example 15) The average particle size is 0.5 μm and the specific surface area is 15.70 m 2 / g aluminum nitride powder raw material 100 parts by mass and an average particle size of 10.2 μm and a specific surface area of ​​0.47 m 2 20 parts by mass of aluminum nitride powder raw material with a concentration of 100 / g were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 1850°C for 20 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain an average particle size of 17.2 μm and a specific surface area of ​​0.22 m 2 Table 2 shows the various measurement results of the aluminum nitride powder.

[0069] (Example 16) The average particle size is 1.0 μm and the specific surface area is 2.81 m 2 / g aluminum nitride powder raw material 100 parts by mass and an average particle size of 7.8 μm and a specific surface area of ​​0.62 m 2 10 parts by mass of aluminum nitride powder raw materials with a concentration of 1 g / g were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 1900°C for 10 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain a granular material with an average particle size of 17.8 μm and a specific surface area of ​​0.21 m 2 Table 2 shows the various measurement results of the aluminum nitride powder.

[0070] (Example 17) The average particle size is 0.5 μm and the specific surface area is 15.70 m 2 / g aluminum nitride powder raw material 100 parts by mass, average particle size 10.2 μm, specific surface area 0.47 m 2 5 parts by mass of a raw material of aluminum nitride powder having a concentration of 100 / g and 0.1 parts by mass of yttrium oxide as an additive were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 1850°C for 10 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain an average particle size of 17.8 μm and a specific surface area of ​​0.21 m 2 Table 2 shows the various measurement results of the aluminum nitride powder.

[0071] (Example 18) The average particle size is 0.5 μm and the specific surface area is 15.70 m 2 / g aluminum nitride powder raw material 100 parts by mass, average particle size 10.2 μm, specific surface area 0.47 m 2 5 parts by mass of a raw material of aluminum nitride powder having a value of / g and 0.1 parts by mass of calcium fluoride as an additive were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 1850°C for 10 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain an average particle size of 18.1 μm and a specific surface area of ​​0.21 m 2 Table 2 shows the various measurement results of the aluminum nitride powder.

[0072] (Example 19) The average particle size is 0.5 μm and the specific surface area is 15.70 m 2 / g aluminum nitride powder raw material 100 parts by mass, average particle size 10.2 μm, specific surface area 0.47 m 2 5 parts by mass of aluminum nitride powder raw material having a value of / g and 5 parts by mass of calcium fluoride as an additive were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 1850°C for 10 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain an average particle size of 18.2 μm and a specific surface area of ​​0.21 m 2 Table 2 shows the various measurement results of the aluminum nitride powder.

[0073] (Example 20) The average particle size is 0.5 μm and the specific surface area is 15.70 m 2 / g aluminum nitride powder raw material 100 parts by mass, average particle size 10.2 μm, specific surface area 0.47 m 2 5 parts by mass of a raw material of aluminum nitride powder having a concentration of / g and 0.1 parts by mass of cesium oxide as an additive were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 1850°C for 10 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain an average particle size of 18.3 μm and a specific surface area of ​​0.21 m 2 Table 2 shows the various measurement results of the aluminum nitride powder.

[0074] (Example 21) The average particle size is 0.5 μm and the specific surface area is 15.70 m 2 / g aluminum nitride powder raw material 100 parts by mass, average particle size 10.2 μm, specific surface area 0.47 m 2 5 parts by mass of aluminum nitride powder raw material having a value of / g and 0.1 parts by mass of calcium carbonate as an additive were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 1850°C for 10 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain an average particle size of 18.5 μm and a specific surface area of ​​0.21 m 2 Table 3 shows the various measurement results of the aluminum nitride powder.

[0075] (Example 22) The average particle size is 0.5 μm and the specific surface area is 15.70 m 2 / g aluminum nitride powder raw material 100 parts by mass, average particle size 10.2 μm, specific surface area 0.47 m2 5 parts by mass of a raw material of aluminum nitride powder having a value of / g and 0.1 parts by mass of lanthanum oxide as an additive were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 1850°C for 10 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain an average particle size of 18.5 μm and a specific surface area of ​​0.21 m 2 Table 3 shows the various measurement results of the aluminum nitride powder.

[0076] (Example 23) The average particle size is 0.5 μm and the specific surface area is 15.70 m 2 / g aluminum nitride powder raw material 100 parts by mass and an average particle size of 7.8 μm and a specific surface area of ​​0.62 m 2 10 parts by mass of aluminum nitride powder raw materials with a concentration of 100 g / g were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 2000°C for 5 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain a granular material with an average particle size of 18.7 μm and a specific surface area of ​​0.20 m 2 Table 3 shows the various measurement results of the aluminum nitride powder.

[0077] (Example 24) The average particle size is 0.5 μm and the specific surface area is 15.70 m 2 / g aluminum nitride powder raw material 100 parts by mass, average particle size 16.2 μm, specific surface area 0.23 m 2 5 parts by mass of a raw material of aluminum nitride powder having a value of / g and 0.1 parts by mass of calcium fluoride as an additive were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 1900°C for 18 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain a granular material with an average particle size of 26.3 μm and a specific surface area of ​​0.19 m 2 Table 3 shows the various measurement results of the aluminum nitride powder.

[0078] (Example 25) The average particle size is 0.5 μm and the specific surface area is 15.70 m 2 / g aluminum nitride powder raw material 100 parts by mass, average particle size 16.2 μm, specific surface area 0.23 m 2 5 parts by mass of aluminum nitride powder raw material having a value of / g and 0.1 parts by mass of lanthanum oxide as an additive were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 1900°C for 18 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain a granular material with an average particle size of 26.5 μm and a specific surface area of ​​0.19 m 2 Table 3 shows the various measurement results of the aluminum nitride powder.

[0079] (Example 26) The average particle size is 1.0 μm and the specific surface area is 2.81 m 2 / g aluminum nitride powder raw material 100 parts by mass and an average particle size of 18.7 μm and a specific surface area of ​​0.20 m 2 5 parts by mass of aluminum nitride powder raw materials with a concentration of / g were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 2000°C for 8 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain a granular material with an average particle size of 28.8 μm and a specific surface area of ​​0.17 m 2 / g aluminum nitride powder (AL-26). The various measurement results of the aluminum nitride powder are shown in Table 3. Figure 2 shown.

[0080] (Example 27) The average particle size is 0.5 μm and the specific surface area is 15.70 m 2 / g aluminum nitride powder raw material 100 parts by mass and an average particle size of 18.2 μm and a specific surface area of ​​0.21 m 2 15 parts by mass of aluminum nitride powder raw material with a concentration of 1.174 W / g were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 1900°C for 20 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain a granular material with an average particle size of 28.8 μm and a specific surface area of ​​0.17 m 2 Table 3 shows the various measurement results of the aluminum nitride powder.

[0081] (Example 28) The average particle size is 1.0 μm and the specific surface area is 2.81 m 2 / g aluminum nitride powder raw material 100 parts by mass and an average particle size of 17.8 μm and a specific surface area of ​​0.21 m 2 20 parts by mass of aluminum nitride powder raw material with a concentration of 100 / g were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 1950°C for 10 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain an average particle size of 29.4 μm and a specific surface area of ​​0.17 m 2 Table 3 shows the various measurement results of the aluminum nitride powder.

[0082] (Example 29) The average particle size is 0.5 μm and the specific surface area is 15.70 m 2 / g aluminum nitride powder raw material 100 parts by mass and an average particle size of 26.5 μm and a specific surface area of ​​0.14 m 2 10 parts by mass of aluminum nitride powder raw materials with a concentration of 100 g / g were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 1950°C for 12 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain an average particle size of 38.2 μm and a specific surface area of ​​0.11 m 2 Table 3 shows the various measurement results of the aluminum nitride powder.

[0083] (Example 30) The average particle size is 3.0 μm and the specific surface area is 1.79 m 2 / g aluminum nitride powder raw material 100 parts by mass and an average particle size of 28.8 μm and a specific surface area of ​​0.13 m 2 10 parts by mass of aluminum nitride powder raw materials with a concentration of 100 g / g were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 1950°C for 20 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain an average particle size of 39.0 μm and a specific surface area of ​​0.10 m 2 Table 4 shows the various measurement results of the aluminum nitride powder.

[0084] (Example 31) The average particle size is 4.7 μm and the specific surface area is 1.22 m 2 / g aluminum nitride powder raw material 100 parts by mass and an average particle size of 38.2 μm and a specific surface area of ​​0.10 m 2 10 parts by mass of aluminum nitride powder raw materials with a concentration of 100 g / g were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 1950°C for 20 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain an average particle size of 44.0 μm and a specific surface area of ​​0.09 m2 Table 4 shows the various measurement results of the aluminum nitride powder.

[0085] (Example 32) The average particle size is 1.0 μm and the specific surface area is 2.81 m 2 / g aluminum nitride powder raw material 100 parts by mass and an average particle size of 26.4 μm and a specific surface area of ​​0.14 m 2 15 parts by mass of aluminum nitride powder raw material with a concentration of 1.174 W / g were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen was supplied into the device to form a nitrogen atmosphere, and heated at 2100°C for 14 hours. The heating was carried out under normal pressure, and then crushed and oxidized to obtain a granular material with an average particle size of 49.4 μm and a specific surface area of ​​0.05 m 2 Table 4 shows the various measurement results of the aluminum nitride powder.

[0086] (Comparative Example 1) The heating device only contains particles with an average particle size of 1.0 μm and a specific surface area of ​​2.81 m 2 / g aluminum nitride powder, nitrogen gas is supplied into the device to form a nitrogen atmosphere, and heating is performed at 1900°C for 10 hours. The heating is performed under normal pressure, and then the aluminum nitride powder is obtained by crushing and oxidation. The obtained aluminum nitride powder is a very small particle with an average particle size of 2.2 μm, although about 10% of the particles have a surface with a relatively flat contour line. In addition, the smoothness of the above-mentioned flat surface was evaluated, and the result showed that the smoothness was poor. The various measurement results of the aluminum nitride powder are shown in Table 4.

[0087] (Comparative Example 2) The average particle size is 2.0 μm and the specific surface area is 1.93 m 2 / g aluminum nitride powder raw material 100 parts by mass and an average particle size of 3.0 μm and a specific surface area of ​​1.79 m 2 10 parts by mass of aluminum nitride powder raw materials with a concentration of 100 g / g were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen gas was supplied into the device to form a nitrogen atmosphere, and the mixture was heated at 1850° C. for 10 hours. The heating was performed under normal pressure, and the mixture was then crushed and oxidized to obtain aluminum nitride powder. The aluminum nitride powder obtained was very small particles with an average particle size of 3.2 μm, although about 40% of the particles had a surface with a relatively flat contour line. In addition, the smoothness of the above-mentioned flat surface was evaluated, and the result showed that the smoothness was poor. The various measurement results of the aluminum nitride powder are shown in Table 4.

[0088] (Comparative Example 3) The average particle size is 1.0 μm and the specific surface area is 2.81 m 2 / g aluminum nitride powder raw material 100 parts by mass and an average particle size of 3.0 μm and a specific surface area of ​​1.79 m 2 50 parts by mass of aluminum nitride powder raw materials with a concentration of 100 / g were mixed to prepare a raw material mixture. The raw material mixture was placed in a heating device, nitrogen gas was supplied into the device to form a nitrogen atmosphere, and the mixture was heated at 1850° C. for 10 hours. The heating was performed under normal pressure, and the mixture was then crushed and oxidized to obtain aluminum nitride powder. The obtained aluminum nitride powder is a very small particle with an average particle size of 3.7 μm, although it contains about 50% of particles having a surface with a relatively flat contour line. In addition, the smoothness of the above-mentioned flat surface was evaluated, and the result showed that it lacked smoothness. The various measurement results of the aluminum nitride powder are shown in Table 4.

[0089] (Comparative Example 4) Aluminum powder with an average particle size of 7.5 μm and an average particle size of 1.0 μm and a specific surface area of ​​2.8 m 2 / g of aluminum nitride powder were mixed in a ratio of 1:2 to prepare a raw material mixture. The raw material mixture was placed in a reactor and subjected to combustion reaction under nitrogen pressure, and the obtained lumps were broken up to obtain aluminum nitride powder. The average particle size of the obtained aluminum nitride powder was 19.2 μm. Among the particles constituting the aluminum nitride powder, the proportion of particles having a surface with a relatively flat contour line was about 20%. The smoothness of the flat surface of the particles was evaluated and the smoothness was poor. Thus, in Comparative Example 4, the specific aluminum nitride powder containing polyhedral particles having at least two smooth surfaces specified in the present invention was not obtained. The various measurement results of the aluminum nitride powder are shown in Table 4.

[0090]

[0091]

[0092]

[0093]

[0094] In each example, an aluminum nitride powder having an average particle size in the range of 5 to 50 μm is obtained, the aluminum nitride powder includes polyhedral particles having at least two smooth surfaces and a major axis / minor axis ratio in a specific range, and the oxygen concentration is sufficiently low, and has high thermal conductivity. In addition, the resin composition obtained by filling the aluminum nitride powder of each example into a resin has high thermal conductivity and excellent fluidity, and is useful as a heat dissipation material. Description of Reference Numerals

[0095] 11.12 Polyhedral particles a Smooth surface

Claims

1. An aluminum nitride powder having an average particle size of 5 to 50 μm and an oxygen content of 0.5 mass % or less, comprising polyhedral particles having at least two smooth surfaces when observed under a scanning electron microscope at a magnification of 500 times, and wherein the average value of the ratio L / D of the major diameter L to the minor diameter D of the polyhedral particles having a major diameter L of 5 μm or more is in the range of 1.0 to 1.

4.

2. The aluminum nitride powder according to claim 1, wherein The presence ratio of the polyhedral particles is 70% or more.

3. The aluminum nitride powder according to claim 1, wherein In the 2000-fold SEM image of the cross section of the polyhedral particle, the average value M of the maximum value M of the perpendicular distance between the contour line of the smooth surface and the straight line connecting the ends of the contour line in 10 randomly selected particles is A It is less than 0.15μm. 4 . The aluminum nitride powder according to claim 1 , which is for resin filling. 5 . A resin composition comprising the aluminum nitride powder according to claim 1 or 2 and a resin.

6. A method for producing aluminum nitride powder, characterized in that: include: Step 1: prepare a granular material having an average particle size of 0.5 to 5 μm and a specific surface area of ​​1.2 to 16.0 m 2 100 parts by mass of the first aluminum nitride powder raw material having an average particle size of 3 to 40 μm and a specific surface area of ​​0.05 to 1.8 m 2 / g and a ratio SA2 / SA1 of the specific surface area SA2 to the specific surface area SA1 of the first aluminum nitride powder raw material of 0.8 or less, to prepare a raw material mixture; and In step 2, the raw material mixture is heated to 1750 to 2100° C. under supply of an inert gas.

Citation Information

Patent Citations

  • Aluminum nitride powder, production method therefor, and its use

    JP2003119010A

  • Method for evaluating crystalline inorganic particle

    JP2021143968A

  • AlN PARTICLE AND METHOD FOR PRODUCING THE SAME

    JP2022067865A

  • Aluminum nitride particle

    WO2017131239A1

  • Aluminum nitride-based powder and method for producing same

    WO2018216591A1